Epidemiology, presentation and integrated management of scorpion sting envenomation - V. Binorkar, Sandeep; R. Parlikar, Gajanan (International Journal of Pharmacology and Toxicology, 2016)
Scorpion sting is an overwhelming & an endemic public health problem in some rural part of the India. Approximately 1,400 species of the Scorpion are found worldwide. 50 species out of 700, in India, can cause serious illness. Most of the studies have focused on the clinical and epidemiological aspects of scorpion stings. However, the venom of several scorpion species can trigger Cerebral, Cardiovascular & other systemic disturbances which may lead to death. Ayurveda has explained numerous medicinal preparations in the management of Vrishchika Damsha (Scorpion sting). This Paper highlights on the presentation of Scorpion sting and its acceptable prophylaxis and therapeutic protocols according to Ayurveda & conventional medical science.